Associations of Plasma Phospholipid and Dietary Alpha Linolenic Acid With Incident Atrial Fibrillation in Older Adults: The Cardiovascular Health Study. Issue 1 (31st January 2013) - Fretts, Amanda M.; Mozaffarian, Dariush; Siscovick, David S.; Heckbert, Susan R.; McKnight, Barbara; King, Irena B.; Rimm, Eric B.; Psaty, Bruce M.; Sacks, Frank M.; Song, Xiaoling; Spiegelman, Donna; Lemaitre, Rozenn N.
Abstract : Background: Few studies have examined the relationship of α‐linolenic acid (ALA 18:3n‐3), an intermediate‐chain essential n‐3 polyunsaturated fatty acid derived from plants and vegetable oils, with incident atrial fibrillation (AF). Methods and Results: The study population included participants from the Cardiovascular Health Study, a community‐based longitudinal cohort of adults aged 65 or older, free of prevalent coronary heart disease and atrial fibrillation. We assessed the associations of plasma phospholipid and dietary ALA with incident AF using Cox regression. The biomarker analysis comprised a total of 2899 participants, and the dietary analysis comprised 4337 participants. We found no association of plasma phospholipid ALA and incident AF. Comparing each of the second, third, and fourth quartiles to the lowest quartile, the hazard ratios for AF were 1.11 (95% CI, 0.90 to 1.37), 1.09 (95% CI, 0.88 to 1.35), and 0.92 (95% CI, 0.74 to 1.15), after adjustment for age, sex, race, clinic, education, smoking, alcohol, body mass index, waist circumference, diabetes, heart failure, stroke, treated hypertension, and physical activity ( P trend=0.48). When dietary ALA was considered the exposure of interest, results were similar. Conclusions: Results from this prospective cohort study of older adults indicate no association of plasma phospholipid or dietary ALA and incident AF.